Supplementary material 2 from: Nizamutdinov T, Abakumov E, Morgun E (2021) Morphological features, productivity and pollution state of abandoned agricultural soils in the Russian Arctic (Yamal Region). One Ecosystem 6: e68408. https://doi.org/10.3897/oneeco.6.e68408 - Nizamutdinov, Timur; Abakumov, Evgeny; Morgun, Evgeniya (Zenodo, 2021)
Estimated scales of nutrient content in soil